Sustainable Tourism in the Galapagos Islands: Strategies and Challenges for Conserving Natural Heritage and Tourism for Adults - Quezada-Sarmiento, Pablo Alejandro; Patricia Marisol Chango-Cañaveral; Jadán Guerrero, Janio; Mónica Consuelo Sarauz (My University, 2025)
This research emphasizes the significance of the Galapagos Islands as a unique tourist destination with exceptional biodiversity and valuable natural heritage for adult tourists. It explores how adventurous tourists of different ages, particularly older adults, have become a crucial source of economic income and a catalyst for the development of local communities. The study also discusses the importance of implementing sustainable tourism practices to protect fragile ecosystems and the islands’ endemic biodiversity. It also addresses challenges such as the introduction of alien species, the impact of increasing tourism demand on resources and infrastructure, and the crucial need for a balance between economic development and environmental conservation. The research examines how sustainable tourism has significantly benefitted local communities, not only in terms of employment generation but also in promoting environmental awareness and community participation, instilling hope and optimism for a sustainable, prosperous future. The research concludes by emphasizing the need for a holistic and adaptive approach to ensure that the Galapagos Islands remain a model of sustainable tourism, protecting its natural heritage and ensuring a sustainable, prosperous future for its inhabitants and adult tourists.
Keywords: Adults; Biodiversity; Development; Environmental conservation; Galapagos; Tourism